2004
DOI: 10.1097/01.mej.0000127641.93092.82
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous tension pneumopericardium

Abstract: A 29-year-old man presented to the accident and emergency department complaining of a sudden onset of chest and upper abdominal pain. He had a past history of intravenous drug abuse and a previous stab wound to the left hypochondrium that had required laparotomy. On arrival he was distressed with grunting respiration. Initial chest X-ray showed a pneumopericardium. Despite titrated doses of opiate analgesia he became increasingly distressed, agitated and dyspnoeic. Repeat chest X-ray demonstrated an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Macroperforations of the pericardium may be caused by penetration or blunt trauma and canfollow thoracic or abdominal surgery. 2,5,6,[8][9][10][11] In the first case, a penetrating injury causing a communication between a bronchus and the pericardium was the likely cause of injury. In the experience of the senior author, visualising a communication between bronchus and pericardium during bronchoscopy can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Macroperforations of the pericardium may be caused by penetration or blunt trauma and canfollow thoracic or abdominal surgery. 2,5,6,[8][9][10][11] In the first case, a penetrating injury causing a communication between a bronchus and the pericardium was the likely cause of injury. In the experience of the senior author, visualising a communication between bronchus and pericardium during bronchoscopy can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Although pneumopericardium may develop due to high-pressure mechanical ventilation, mediastinal tumors, tuberculosis, or gastro pericardial fistula may also develop iatrogenically due to endomyocardial biopsy or after pacemaker implantation. 2 …”
Section: Discussionmentioning
confidence: 99%
“…These areas are mostly the pleural space, tracheobronchial tree, or the gastrointestinal tract. 2 , 3 In the literature, there are only a few pneumopericardium cases caused by chemotherapy administered for a metastatic lung disease. Ours is one of them.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the 82 cases were due to penetrating trauma. Boyce et al 4 reported another case of a stab wound to the left hypochondrium presenting with tension pneumopericardium secondary to perforated gastric ulcer in the pericardial sac several years after the initial injury. This is a report of the fourth case of such hernia after a stab wound.…”
Section: Discussionmentioning
confidence: 99%